Etiology and Medication of Hospitalized Children With Hypertension: A Retrospective Study - Chenhong Jia; Weijing Ding; Xiangyu Ding (The Journal of Clinical Hypertension)
ABSTRACT With the increasing incidence of hypertension in children, the lack of high‐quality research data on antihypertensive drugs in pediatric patients restricts treatment options for clinicians and can lead to suboptimal outcomes. We conducted a retrospective analysis of clinical data from hospitalized pediatric patients diagnosed with hypertension and treated with antihypertensive drugs in the past 3 years. The study included 203 pediatric patients (119 males and 84 females), with an average age of 8.9 ± 4.7 years (range: 0.1–17 years). Clinical symptoms of hypertension were observed in 132 participants (65.0%), and the conditions in all cases were classified as primary or secondary hypertension. Renal causes (71 patients, 35.0%) and drug‐induced factors (39 patients, 19.2%) were the main causes of secondary hypertension. Nifedipine (137 patients, 67.5%) was the most commonly prescribed medication, followed by captopril (84 patients, 41.4%). Multiple antihypertensive medications were prescribed to 99 participants (48.8%), and blood pressure returned to normal in 111 patients (54.7%). Hypertension‐related organ damage was observed in 47 patients (23.2%). Timely diagnosis and treatment of hypertension are critical to prevent organ damage in pediatric patients. Although nifedipine was widely used in this pediatric cohort, the appropriateness of this treatment remains unclear. Emphasis should be placed on monitoring target organs affected by pediatric hypertension, and post‐discharge antihypertensive treatment should include thorough follow‐ups and documentation.